Mineral and inflammatory disturbances on reproductive system triggered by cadmium exposure - Cupertino, Marli do Carmo (2016)
The study of toxicity mechanism caused by the environmental pollutants is a broad research field. The toxic effect of Cadmium (Cd) in reproductive system is not a novel issue, but many gaps still remain to be filled, especially on the mechanisms by which the Cd triggers injuries. The objective of this study was to evaluate the inflammatory and mineral pattern presented by rats exposed to four low doses of Cd and to analyze after initial inflammatory phase and before chronic fibrosis. Thus, adult male rats were intraperitoneally exposed to single doses of Cd chloride, along with a saline control group: 1- 0.9% NaCl; 2- CdCl 2 1.1 mg/kg (0.67 mg Cd/kg); 3- CdCl 2 1.2 mg/kg (0.74 mg Cd/kg); 4-CdCl 2 1.4 mg/kg (0.86 mg Cd/kg); e 5- CdCl 2 1.8 mg/kg (1.1 mg Cd/kg). Seven days after exposure, blood and reproductive organs were collected and the following analyses were performed: biometric, morphometric and stereological, oxidative stress, lipid and protein peroxidation, DNA damage, ultrastructure by transmission and scanning electron microscopy, dosage of tissue minerals, serum testosterone, inflammatory cytokines and histopathological analyses that included markings for apoptosis and calcification. It was observed that the inflammatory pattern is marked by neutrophils in intertubule and basal environment without changing markers of lipid peroxidation, suggesting the absence of damage in the Sertoli cell barrier. Markers of oxidative stress and cytokines presented changes indicating this is one of the mechanisms by which lesions are induced. There was reduction in testosterone production and changes in the Leydig parameters. Intense apoptosis and calcification of germ cells and collagen fibers were observed. There was increase of calcium in the tissue along with the increase of Cd dose, but the other minerals decreased. Histopathology and morphometric, stereological and biometric changes increased depending on the dose. We concluded that the injuries caused by Cd are dose-dependent and mineral and inflammatory pathways play a key role in the development of lesions.